Analisis Yuridis Pasal Perzinaan dalam KUHP Baru dalam Perspektif Asas Pembentukan Peraturan Perundang-Undangan - Adtila Prawoko; Ab’dan Syukur; Nadia Putri Kustiono; Anita Nur Amaliyah; Kuswan Hadji (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
The enactment of Law Number 1 of 2023 concerning the Criminal Code brought fundamental changes to the regulation of the crime of adultery in Indonesia. The expansion of the scope of criminalization, including regulations regarding extramarital relationships, has given rise to debate regarding its compliance with the principles of the formation of laws and regulations and its impact on criminal law enforcement. This study aims to analyze the provisions of the adultery article in the new Criminal Code from the perspective of the principles of the formation of laws and regulations and assess its implications for the effectiveness of the criminal justice system. This study uses a normative legal research method with a legislative and conceptual approach. Legal materials were obtained through literature studies and analyzed qualitatively and juridically. The results show that the regulation of the crime of adultery in the new Criminal Code has a clear normative purpose, but still leaves issues regarding the clarity of formulation, legal certainty, and potential human rights violations. Furthermore, the application of the adultery article has the potential to create obstacles in law enforcement practices, particularly related to evidence, caseload, and the legitimacy of the criminal justice system. Therefore, further evaluation is needed to ensure that these regulations align with the principles of sound legislative development and ensure legal justice.